Girl waits with gun [compact disc, unabridged] - Stewart, Amy (Stewart, Amy. Kopp sisters novel., 2015)
Living in virtual isolation years after the revelation of a painful family secret, Constance Kopp is terrorized by a belligerent silk factory owner and fights back in ways outside the norm for early twentieth-century women.